2021
DOI: 10.21608/jpd.2021.211859
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF DIFFERENT SUBSTRATE MEDIA AND IRRIGATION ON FLOWERING AND PRODUCTION OF STRAWBERRY (Fragaria spp)

Abstract: The present experiment was carried out in greenhouse during 2018/2019 and 2019/2020 seasons to determine the effects of substrates media / combination and macro and micro nutrients within irrigation water. Uniform runners of strawberry cv. chandler were selected and planted in 12 and 13 th October 2018 and 2019 seasons, respectively, at a distance of 20 cm x 20 cm in 1m x 1m beds filled with eight different growing media combinations viz, sand (100%), peat moss (100%), vermiculite (100%), perlite (100%), peat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
2
4
0
Order By: Relevance
“…According to Tabatabaei et al [20] the media consisted of perlite, which increased plant height in strawberries. A similar result was reported by Hassan et al [21] that utilizing coconut husk resulted in the largest plant height in strawberry, whereas soil cultivation produced the lowest. Kumar et al [22] indicates that highest plant height, was significantly recorded in Winter Dawn than Sweet Charlie in the potting substrates which consist of soil, vermicompost and cocopeat.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…According to Tabatabaei et al [20] the media consisted of perlite, which increased plant height in strawberries. A similar result was reported by Hassan et al [21] that utilizing coconut husk resulted in the largest plant height in strawberry, whereas soil cultivation produced the lowest. Kumar et al [22] indicates that highest plant height, was significantly recorded in Winter Dawn than Sweet Charlie in the potting substrates which consist of soil, vermicompost and cocopeat.…”
Section: Resultssupporting
confidence: 88%
“…It was followed by C1M1: earthen pots {cocopeat + perlite + vermicompost (1:1:2) which had 25.50 leaves per plant, whereas, the minimum number of leaves per plant of 10.00 was noted in C3M4: thermoform pots {soil + sand + FYM (1:1:1)}. Hassan et al [21] found that utilizing coconut husk resulted in the largest number of leaves in strawberry whereas, soil cultivation produced the lowest. According, to Selda and Anapali [27] the number of leaves decreased as the soil amount increased in the media.…”
Section: Resultsmentioning
confidence: 99%
“…These nutrients uptake in plant led to biosynthesis of different growth regulators like Auxin which promote flowering in the plants. Similar results were observed by Hassan et al [16] while working on strawberry and Kumar et al [17] while working on calendula.…”
Section: No Of Flowerssupporting
confidence: 89%
“…Prasad et al (2021) also revealed that addition of compost (of spent mushroom) in growing media improves morphology and yield in strawberry. Hassan et al (2011) also reported that mixture of different organic substrates was beneficial in obtaining good fruit size of strawberry (cv. Festival).…”
Section: Discussionmentioning
confidence: 96%
“…Soil and organic manures combined with cocopeat were found very useful in this study as cocopeat has likely helped maintaining better water retention, since proper density and porosity of the substrates play a decisive role for its usability for strawberry cultivation (Ameri et al 2012). Hassan et al (2011) observed highest number of leaves and plant height in coconut husk medium, while lowest in soil. The number 1 Krishi Vigyan Kendra, National Horticultural Research and Development Foundation (NHRFDF), Ujwa, New Delhi; 2 Amity Institute of Horticulture Studies and Research, Amity University, Noida; Uttar Pradesh; 3 Division of Fruit Science, SKUAST-Kashmir, Srinagar, Jammu and Kashmir; 4 ICAR-Central Arid Zone Research Institute, Jodhpur, Rajasthan.…”
mentioning
confidence: 79%